Responsibility and Coteaching: A Review of Warts and All - Ian Stith (Forum: Qualitative Social Research, 2006)
Coteaching, like any student teaching method, is filled with ethical questions and communicative problems. With the metalogue presented in "Warts and all: Ethical dilemmas in implementing the coteaching model" as the base this paper focuses on the experience of Matt, the student teacher, and the ethically issues he faced as a coteacher. In line with the experiences of Matt I reanalyze the question of how change can be implemented given the variety of philosophies of education inherent in a large-scale project. Finally, the cogenerative dialogue is presented as an ethical tool to increase the quality and frequency of communication between participants. URN: urn:nbn:de:0114-fqs0604228